Uses and gratifications of trilingual newspapers in Sabah - Elizabeth Joanny Openg; Siti Ezaleila Mustafa; Mohammad Rashidi Pakri (Penerbit Universiti Kebangsaan Malaysia, 2023)
There are at least 33 periodicals have been established in Sabah since 1883. These include various monolingual, bilingual, and trilingual newspapers published between 1883 and 2022 in various formats including the trilingual newspaper’s format The focus of this study is to investigate the roles of local trilingual newspapers in Sabah and, at the same time, to distinguish between the gratification sought (gs) and the rewards received (gratifications obtained) by readers of the selected local trilingual newspapers in Sabah namely The New Sabah Times, Daily Express, and Borneo Post. The mixed-method research method was implemented to meet the research objectives. 159 respondents were randomly selected to participate in the online and offline questionnaires, and 10 of them were randomly selected to answer the interview. The findings of this study show that readers chose trilingual newspapers to satisfy their cognitive, social-integrative, escapist, and affective needs. Therefore, this study wishes to provide evidence to the local newspaper press to continue the Kadazandusun column in a way that can satisfy the needs of their readers.